Nurse Anxiety of Handling Patient Covid-19 in Emergency Department - Nur, Mangsur M; Andarini, Sri; Ismail, Dina Dewi Sartika Lestari (Universitas Aisyah Pringsewu, 2022)
Coronavirus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. Coronavirus can cause mild disorders of the respiratory system, severe lung infections, and even death. This study aims to determine the relationship between knowledge, workload, an increasing number of patients, risk of exposure and infrastructure with nurses' anxiety. This study used an analytic observational design with a cross-sectional approach. The sample is 61 nurses, the sampling technique uses Total Sampling, and the analysis uses the Spearman Rank test, Pearson correlation. The results of this study indicate that there is a relationship between knowledge (p = .002, r = - .389), workload (p-value = .047, r = .256), an increase in the number of patients (p-value = .009, r = .333), risk exposure (p-value = .048, r = - .254), and infrastructure (p-value = .040, r = - .264) with anxiety. There is a significant relationship between knowledge, workload, an increasing number of patients, risk of exposure, and facilities and infrastructure with anxiety. The hospital needs to prepare adequate infrastructure and facilities for medical personnel who are on the front line, especially related to personal protective equipment.Abstrak: Virus Corona atau severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2) merupakan virus yang menyerang sistem pernapasan. Virus Corona bisa menyebabkan gangguan ringan pada sistem pernapasan, infeksi paru-paru yang berat, hingga kematian. penelitian ini bertujuan untuk mengetahui hubungan pengetahuan, beban kerja, peningkatan jumlah pasien, resiko paparan dan sarana prasarana dengan kecemasan perawat. Penelitian ini menggunakan desain observasional analitik dengan pendekatan cross sectional. Sampel sebanyak 61 orang perawat, tehnik sampling menggunakan Total Sampling, dan analisis menggunakan uji Spearman Rank, korelasi pearson. Hasil penelitian ini menunjukkan adanya hubungan antara pengetahuan (p= .002, r= - .389), beban kerja (p value= .047, r= .256), peningkatan jumlah pasien (p value = .009, r = .333), resiko paparan (p value=.048, r = -.254), dan sarana prasarana (p value= .040, r= - .264) dengan kecemasan. Terdapat hubungan signifikan antara Pengetahuan, beban kerja, peningkatan jumlah pasien, resiko paparan, dan sarana dan prasarana dengan Kecemasan. pihak rumah sakit perlu mempersiapkan sarana dana prasarana yang memadai buat tenaga medis yang berada di garda terdepan terutama terkait dengan alat pelindung diri.